ENGARUH KOMPONEN INTELLECTUAL CAPITAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR CONSUMER NON-CYLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Mulya Adi; Maryati, Ulfi; Chandra, Novrina (Journal of Applied Accounting And Business, 2025)
This study aims to test the influence of intellectual capital, and the company's measure against the company's financial performance as measured by Return On Assets (ROA). The research method used is multiple linear regression with sampling technique purposive sampling which resulted in a sample of 47 companies consumer non-cyclicals which is listed  on the Indonesia Stock Exchange (IDX). This research was conducted using the observation year, namely 2021-2023. The type of data used is secondary data. Data is obtained from the company's annual financial statements taken from www.idx.co.id. The results of this study partially show that the components of the intellectual capital (VACA, VAHU, STVA) affect the company's financial performance (ROA), while the size of the company has no effect on the company's financial performance (ROA). The results of the hypothesis test simultaneously show that VACA, VAHU, STVA, and company size together affect the company's financial performance (ROA).